Perancangan Antarmuka Aplikasi Perangkat Bergerak Pengelolaan Sampah MyGarbage menggunakan Metode Human Centered Design (HCD) (Studi Kasus: Warga Perumahan Juanda Harapan Permai, Sidoarjo) - Muhammad Najmi Faisal; Agi Putra Kharisma; Fais Al Huda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In Indonesia, the most significant component of waste based on waste sources comes from household waste. Based on the problems that exist in the Juanda Harapan Permai housing, there are still many residents who have difficulty managing waste. In addition, the ease of interface in an application design becomes an important factor for a good user experience. Therefore we need an interface solution for a platform that is flexible and can be accessed anywhere. This study designed an interface for the MyGarbage waste management application using the Human-Centered Design (HCD) method. In interface design, research results are obtained through wireframe, high fidelity, and prototype design. The results of the usability testing get results from the effectiveness aspect using the success rate metric of 88.67%, the results from the efficiency aspect using the Overall Relative Efficiency metric of 100%. The results from the satisfaction aspect using the System Usability Scale (SUS) method an average of 72,5 with Good and High Acceptable categories. The results of the evaluation of user experience using the User Experience Questionnaire (UEQ), the attractiveness scale results in the Excellent category, the clarity scale in the Above Average category, the efficiency scale in the good category, the accuracy scale in the excellent category, the stimulation scale in the Excellent category, and the novelty scale in the good category. In the future, for further research, the application interface design is continued into coding stage.